2019
DOI: 10.3390/medicina55070367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Females’ Reproductive Factors on Pituitary Gland Size in Women at Reproductive Age

Abstract: Background and Objectives: The brain imaging of the pituitary gland in females has shown a change in pituitary size and volume in the female's population. It has been proven that the pituitary gland is affected by pregnancy, giving birth, and hormone-related factors. Therefore, this study aimed to evaluate the factors which may have an impact on the pituitary size in females at reproductive age and compare the pituitary size in females with a history of pregnancy, those at the postpartum period, and nullipara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…In our study, the nulliparous females had a larger PG than other groups of parity. This finding is consistent with Daghighi et al, (13) who stated that the gland's volume is greatest in nulliparous women.…”
Section: Fig 5 Linear Relationship Between Volume and Puberty Agesupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the nulliparous females had a larger PG than other groups of parity. This finding is consistent with Daghighi et al, (13) who stated that the gland's volume is greatest in nulliparous women.…”
Section: Fig 5 Linear Relationship Between Volume and Puberty Agesupporting
confidence: 92%
“…There was an insignificant inverse correlation between the depth, the volume of PG with age, puberty, and parity. In contrast, Daghighi et al (13) found that gravidity and parity had a significant negative impact on PG volume (P<o.o1). The insignificant relationship in our study may be due to the small sample size.…”
Section: Fig 5 Linear Relationship Between Volume and Puberty Agementioning
confidence: 85%
“…In a study of 208 healthy women, chronic intake of oral contraceptives was associated with a minimal reduction in mean pituitary height (0.03 mm; P . .05) (24) and thus also unlikely to account for the 0.6-mm loss of mean pituitary height in our study. Chronic pituitary apoplexy is another potential cause of pituitary height loss (25) but has not been emphasized in the literature for astronauts.…”
Section: Discussionmentioning
confidence: 57%